PERSEPSI SUAMI DAN ISTERI TERHADAP KEKERASAN DALAM RUMAH TANGGA - Moerti Hadiati (Perspektif, 2003)
The objective of this research is to know how far the perception of husband and wife about violence in household. It is necessary to conduct this research since the marriage is a tie of inner self and outer world between a man and a woman as a couple for the sake of building a happy and everlasting family (household) in the one God (pasal 1 Undang-Undang No. 1 Tahun 1974). The word ‘household ‘ covers an understanding that gives a description of peace and love feeling. Strangely, in a household that seems to be harmonized and happy, the violence action sometimes still happens. Based on the fact, this research mainly focused on the husband's violence to his wife.